Sampling Volcanic Plume Using a Drone-Borne SelPS for Remotely Determined Stable Isotopic Compositions of Fumarolic Carbon Dioxide - Tsunogai, Urumu; Shingubara, Ryo; Morishita, Yuhei; Ito, Masanori; Nakagawa, Fumiko; Yoshikawa, Shin; Utsugi, Mitsuru; Yokoo, Akihiko (Frontiers in Earth Science, 2022)
Recently, we developed a drone-borne automatic volcanic plume sampler called SelPS, wherein an output signal from a sulfur dioxide (SO2) sensor triggered a pump to collect plume samples when the SO2 concentration exceeded a predefined threshold. In this study, we added a radio transmission function to the sampler, which enabled our operator to monitor real-time SO2 concentration during flights and thus obtain more concentrated volcanic plume samples through precise adjustment of the hovering position. We attached the improved SelPS to a drone at Nakadake crater, Aso volcano (Japan), and successfully obtained concentrated volcanic plume samples ejected from the crater, showing higher concentrations of both molecular hydrogen (H2) and carbon dioxide (CO2) than those manually acquired in flasks at the crater rim. Additionally, we found a significant linear correlation between the reciprocal of the concentration and isotopic ratios for the 2H/1H ratios of H2, 18O/16O ratios of CO2, and 13C/12C ratios of CO2 within the plume samples. Based on the isotopic ratios of fumarolic H2 (δ2H = –239 ± 6 ‰) and fumarolic CO2 (δ13C = –3.58 ± 0.85 ‰ and δ18O = +22.01 ± 0.68 ‰) determined from the linear correlations, we estimated the apparent equilibrium temperatures with magmatic H2O, assuming hydrogen isotope exchange equilibrium between H2 and H2O (AETD = 629 ± 32 °C) and oxygen isotope exchange equilibrium between CO2 and H2O (AET18O = 266 ± 65 °C). AET18O was significantly lower than the AETD in the crater. While the original temperature was 600 °C or more, most volcanic gases cooled just beneath the vents in the crater to temperatures around the boiling point of water.